Study to measure alcohol related attitudes and drinking behaviours in rural Sabah - Naing Oo Tha; Wendy Diana Shoesmith; Khin Saw Naing; Ahmad Faris Abdullah; Roslee Abbas (Universiti Malaysia Sabah, 2009)
Alcohol related problems are the biggest cause of life years lost to disability in Malaysian men· Alcohol use is an important part of the culture of many of the ethnic groups of Sabah. It is widely believed that the alcohol consumption in rural Sabah is high, since a large amount of alcohol related harm is seen in the health system there. Objectives of this study are to estimate the prevalence of alcohol consumption in the study area.to determine the magnitude of harmful drinking, to explore into the factors associated with alcohol consumption.to determine the knowledge and attitude towards alcohol among different ethnic groups.to develop recommendation for future health intervention to combat against alcohol problem in the study areas. A Community-based Cross sectional study was conducted from 2009 Oct -2011 Oct for 2 years in 4 areas of rural Sabah in northern Borneo; Kudat, Kota Marudu, Pitas and Kotabelud. FGDs( Qualitative ) and questionnaires survey with face to face interview( Quantitative ) methods were used by trained local Research Assistants. Survey questionnaire was developed after qualitative survey and designed to detect alcohol consumption and other informations together with the AUDIT screening instrument .This study can find out find out which factors put people at risk of alcohol abuse and dependence.the knowledge and attitudes towards drinking, in particular how much alcohol subjects perceive to be an unhealthy amount, moral perceptions of alcohol use, perceptions about the importance of alcohol to their culture in northern rural community , Sabah.